Utilization of Instagram Social Media in Health Promotion Activities at Hasan Sadikin Hospital Bandung - Yustikasari Yustikasari; Renata Anisa; Retasari Dewi; Fajriani Ananda (JURNAL PROTEKSI KESEHATAN, 2023)
Hospitals must carry out Hospital Health Promotion. By using social media, hospitals can convey various health information to patients, patient's families, and society. This study aimed to determine the use of Instagram social media in the Health Promotion installation at Hasan Sadikin Hospital, Bandung. Data collection techniques used are interviews, observation and documentation studies. The method in this research is descriptive qualitative. The study results: first, the Health Promotion Installation of Hasan Sadikin Hospital Bandung has used Instagram social media well to convey health information. Second, the health promotion content presented on social media accounts is divided into 4 (four): announcement, health promotion, event, and health day commemoration. The conclusion of the research is Health Promotion at Hasan Sadikin Hospital has made content management well, but what can be improved is the objective, message, and timeline of posting frequency.